Sievert-type measurement and acquisition system for the study of hydrogen storage in solids - Runco, Jorge (2013)
This paper shows the development and implementation of a system to determine and analyze parameters of interest in the study of hydrogen absorption and desorption mechanisms in solids using the Sievert volumetric method. The experiment is controlled through a PC-type computing system by automatically measuring, controlling, recording and graphing the evolution of variables (pressures and temperatures) according to a set of previously programmed parameters. The manual monitoring, adjustment and operation option is also available to tune the experiment. The software was developed in a high-level programming language (Delphi) which offers the user a graphical interface typical of visual languages. In addition, results for applying the present system to typical ternary hydrides are presented.